(untitled) (Research, Society and Development, 2020)
This study aimed to promote improvements through the implementation of a combination of quality tools (checklists, brainstorming, Ishikawa diagram, flowchart, program 5S, 5W1H, PDCA, training, and Good Manufacturing Practices (GMP) in a small pasta industry in Maringá - Paraná, Brazil. The industry is located in the Northwest of Paraná, Brazil, and has a processing capacity of 5000 units of “salgados" per hour. The implementation of the quality tools was carried out according to the stages of the PDCA cycle (plan, do, action, and check). The effectiveness of the measures adopted was measured by comparing the total percentages of conformities and non-conformities before and after the implementation of the tools. The results showed improvements in the processes and products of the industry, due to the significant increase in compliance to 79,04 %, while before the implementation of the tools it was 56,94%. Therefore, the results indicated that the implementation of quality tools provided improvements, as it impacted the increase in compliance with the requirements required by the legislation (RDC 275 from ANVISA), as well as changed the general organization and quality of the industry.